Intragenic ERG Deletions Do Not Explain the Biology of ERG-Related Acute Lymphoblastic Leukemia - Potuckova, Eliska; Zuna, Jan; Hovorkova, Lenka; Starkova, Julia; Stary, Jan; Trka, Jan; Zaliova, Marketa (PloS one, 2016)
Intragenic ERG deletions occur in 3-5% of B-cell precursor acute lymphoblastic leukemia, specifically in B-other subtype lacking the classifying genetic lesions. They represent the only genetic lesion described so far present in the majority of cases clustering into a subgroup of B-other subtype characterized by a unique gene expression profile, probably sharing a common, however, not yet fully described, biological background. We aimed to elucidate whether ERG deletions could drive the specific biology of this ERG-related leukemia subgroup through expression of aberrant or decreased expression of wild type ERG isoforms. We showed that leukemic cells with endogenous ERG deletion express an aberrant transcript translated into two proteins in transfected cell lines and that one of these proteins colocalizes with wild type ERG. However, we did not confirm expression of the proteins in acute lymphoblastic leukemia cases with endogenous ERG deletion. ERG deletions resulted in significantly lower expression of wild type ERG transcripts compared to B-other cases without ERG deletion. However, cases with subclonal ERG deletion, clustering to the same ERG deletion associated subgroup, presented similar levels of wild type ERG as cases without ERG deletion. In conclusion, our data suggest that neither the expression of aberrant proteins from internally deleted allele nor the reduced expression of wild type ERG seem to provide a plausible explanation of the specific biology of ERG -related leukemia subgroup.
Keywords: Transcriptional Regulator ERG; HeLa buňky; delece genu; Protein Isoforms; Gene Expression Regulation, Leukemic; lidé; Precursor Cell Lymphoblastic Leukemia-Lymphoma; HeLa Cells; regulace genové exprese u leukemie; protein - isoformy; Gene Deletion; Humans; akutní lymfatická leukemie; transkripční regulátor ERG